The ocean boundary layer beneath Larsen C Ice Shelf: insights from large-eddy simulations with a near-wall model - Vreugdenhil, Catherine A.; Taylor, John R.; Davis, Peter E. D.; Nicholls, Keith W.; Holland, Paul R.; Jenkins, Adrian (Journal of Physical Oceanography, 2022)
The melt rate of Antarctic ice shelves is of key importance for rising sea levels and future climate scenarios. Recent observations beneath Larsen C Ice Shelf revealed an ocean boundary layer that was highly turbulent and raised questions on the effect of these rich flow dynamics on the ocean heat transfer and the ice shelf melt rate (Davis and Nicholls 2019). Directly motivated by the field observations, we have conducted large-eddy simulations (LES) to further examine the ocean boundary layer beneath Larsen C Ice Shelf. The LES was initialised with uniform temperature and salinity (T/S) and included a realistic tidal cycle and a small basal slope. A new parameterization based on Vreugdenhil and Taylor (2019) was applied at the top boundary to model near-wall turbulence and basal melting. The resulting vertical T/S profiles, melt rate and friction velocity matched well with the Larsen C Ice Shelf observations. The instantaneous melt rate varied strongly with the tidal cycle, with faster flow increasing the turbulence and mixing of heat towards the ice base. An Ekman layer formed beneath the ice base and, due to the strong vertical shear of the current, Ekman rolls appeared in the mixed layer and stratified region (depth ≈ 20–60m). In an additional high-resolution simulation (conducted with a smaller domain) the Ekman rolls were associated with increased turbulent kinetic energy, but a relatively small vertical heat flux. Our results will help with interpreting field observations and parameterizing the ocean-driven basal melting of ice shelves.